The Psychological Prose and Edwardian Novel of Henry James in the Intertext of Modernist Prose - Kholmurod qizi, Israilova Nargiza (European Journal of Life Safety and Stability (2660-9630), 2023)
The circle of writers who influenced the formation of psychological prose of modernism in the late 19th and early 20th centuries can be imagined both very wide and narrow: literary sources and influences are the nature of the matter. Not only Oscar Wilde and Walter Peter, Joseph Conrad and R. L. Stevenson, but also George Meredith and George Eliot can be included in this circle on one basis or another. And three more names are undoubtedly included in the intertext: Henry James, Thomas Gardy and Marcel’ Proust. There is clear evidence of this.